Neill of Summerhill: an Educational Philosopher for Personal Responsibility - Swartz, Ronald (Revista Hipótese, 2018)
For those who take on the task of trying to make the ideas associated with the personal responsibility tradition a part of their lives, the work of Neill can become one place to begin to see that learning to “let people live in their own way” may at times be aided by a learning environment that is a fallible liberal democratic self-governing community. And the learning community that Neill founded nearly a hundred years ago has indeed helped to demonstrate that it is possible for many young people to get a valuable, meaningful, and worthwhile education if they are lucky enough to just “hang around” a school such as Summerhill.
Keywords: Summerhill; Neill; Philosophy